Gold nanoparticles for cancer theranostics — A brief update - Ning Zhao (Journal of Innovative Optical Health Sciences, 2016)
Gold nanoparticles (AuNPs) exhibit superior optical and physical properties for more effective treatment of cancer through incorporating both diagnostic and therapeutic functions into one single platform. The ability to passively accumulate on tumor cells provides AuNPs the opportunity to become an attractive contrast agent for X-ray based computed tomography (CT) imaging in vivo. Because of facile surface modification, various size and shape of AuNPs have been extensively functionalized and applied as active nanoprobes and drug carriers for cancer targeted theranostics. Moreover, their capabilities on producing photoacoustic (PA) signals and photothermal effects have been used to image and treat tumor progression, respectively. Herein, we review the developments of AuNPs as cancer diagnostics and chemotherapeutic drug vector, summarizing strategies for tumor targeting and their applications in vitro and in vivo.